Protection of the Rights of the Owners of Common Property in an Apartment Building - Olesya S. Filippova (Сибирское юридическое обозрение, 2016)
The article is devoted to the analysis of civil and housing legislation in the sphere of the protection of the rights of owners of the common property of apartment buildings. Critical evaluation is given to the criteria, сreated by judicial practice, in order to determine whether the basement of such a building may be owned by one person.